[PP.06.03] RESISTANT HYPERTENSION IN VERONA: A COLLABORATIVE POPULATION-BASED OBSERVATIONAL STUDY. (September 2016) - Idolazzi, C.; Fondrieschi, L.; Fava, C.; Delva, P.; Romano, S.; Celebrano, M.; Minuz, P.
Abstract : Objective: Resistant hypertension, is defined as an inadequate blood pressure control despite treatment with a diuretic combined with two different antihypertensive drugs, or requirement of at least four antihypertensive drugs. This clinical condition may confer high cardiovascular risk. Aim of the observational study was to evaluate the prevalence of resistant hypertension and the association with cardiovascular risk factor or disease in the Verona metropolitan area, matching data concerning the clinical characteristics of adult population with information on drug exposure. Design and method: Eleven family doctors, using the electronic medical record software "Millewin", retrieved anonymised data concerning blood pressure, diagnosis of hypertension and treatments from a population database consisting of 17502 adult subjects of either sex. The prevalence of resistant hypertension was estimated considering patients who had been consecutively treated with at least four antihypertensive medications, regardless of blood pressure values, during the previous fifteen months. Further search concerning the clinical characteristics associated with resistant hypertension was performed in a simple random sample of 55 patients 18–79 years old by examining medical notes and interviewing. Results: The prevalence subjects with diagnosis of hypertension was 21.9% (3469 patients), the prevalence of those treated with four antihypertensive drugs was 2, 1% (359 patients), approximately 10% of the whole hypertensive population. High prevalence of diabetes mellitus (53%) and hyperlipidaemia (83%) was found in association with resistant hypertension. As for end organ damage, high prevalence of carotid artery stenosis (45%), ischemic heart disease (43%) and left ventricular hypertrophy (40%) was observed in patients with resistant hypertension. Blood pressure was higher than 140/90 mmHg in 58% of patients in spite of treatment with four or more different antihypertensive drugs. Conclusions: Patients with resistant hypertension are characterised by a very high attributable cardiovascular risk, due to high prevalence of cardiovascular risk factors and overt organ damage and cardiovascular disease. This finding calls for an effective clinical management of resistant hypertension based on a close collaboration between family doctors and hypertension specialists.